Simulação em dinâmica molecular de Car-Parrinello da interação do íon lítio no solvente dimetilcarbonato - (:unkn) unknown (Universidade Estadual de Goiás, 2009)
Technological progress has had a very high incentive to meet the needs for electronic devices smaller and smaller, in terms of mass and volume, with better performance and greater durability, and safety. Among the many examples of these types of devices may be cited as secondary batteries lithium-ion contained in a vast field of study since the 70's in order to obtain materials that provide high energy density and better performance. Cathode, anode and electrolyte materials has been observed in great detail in order to understand more clearly the functioning of that body and get better results over the life cycle of these devices. Car-Parrinello molecular dynamics simulations of conformational structures of the molecule of dimethyl carbonate were carried out in order to know in greater depth the characteristics of it. It enables us to carry out a comparative study of the values of fictitious mass and the size of time step in order to obtain a control adiabaticity of systems. Were also evaluated systems containing Nosé-Hoover thermostats in order to establish whether there is a direct relationship with the control of the adiabaticity. The structural properties and dynamic structures of [Li(DMC)]+ and [Li(DMC)4] + were determined. The [Li(DMC)]+ structure was the basis for understanding the distortions made by the presence of lithium ion on the molecule of dimethyl carbonate. The first salvation shell of the lithium ion in dimethyl carbonate was then evaluated and observed that the structure obtained by the same promotes efficient transport of a lithium ion electrode to the other during the process of loading and unloading in an secondary lithium ion battery.
Keywords: Baterias Recarregáveis; Dimetilcarbonato; Dinâmica Molecular Ab Initio; Rechargeable Batteries; Dimethyl Carbonate; Ab Initio Molecular Dynamics; CIENCIAS EXATAS E DA TERRA::QUIMICA; QUIMICA::FISICO-QUIMICA